Phytochemicals in wild crucifers affect development and reproduction of mustard aphid (Lipaphis erysimi) - BHOI, TANMAYA K; DHILLON, MUKESH K; SAMAL, IPSITA; SINGH, NAVEEN (The Indian Journal of Agricultural Sciences, 2025)
The study was carried out during 2019–2021 at ICAR-Indian Agricultural Research Institute, New Delhi to identify sources of resistance and elucidate the mechanisms of resistance in wild crucifers against the mustard aphid, Lipaphis erysimi (Kaltenbach). A total of 32 genotypes, including 29 wild crucifer spp. and three B. juncea genotypes as checks, were cultivated. Significant differences were observed in the phytochemical composition of 29 wild crucifer genotypes and 3 Brassica juncea check genotypes, which influenced various biological traits of L. erysimi. The total nymphal duration of L. erysimi was significantly longer on Crambe abyssinica and Eruca sativa compared to other genotypes, including B. juncea cultivars. Additionally, aphids exhibited extended reproductive and total developmental periods on Diplotaxis viminea and Enarthrocarpus lyratus, while Lepidium sativum showed reduced fecundity and poor progeny survival. Genotypes such as E. sativa, D. assurgens, and C. abyssinica had significantly higher levels of total proteins, sugars, phenols, tannins, total antioxidants, and FRAP. Total proteins and sugars showed a positive correlation with the nymphal period, developmental duration, and fecundity, whereas phenols, tannins, antioxidants, and FRAP exhibited significant negative correlations with these traits and aphid survival. Furthermore, phenols and tannins had the strongest negative impact, explaining 78.14% of the variability in fecundity and 55.93% in offspring survival. Wild crucifers with elevated biochemical defenses, particularly E. sativa, B. tournefortii, L. sativum, abyssinica, and D. assurgens, effectively reduced aphid reproduction and survival, highlighting their potential for breeding aphid-resistant Indian mustard varieties.